Supercritical carbon dioxide (SC-CO2) extraction of palm kernel oil from palm kernel - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Abd Kadir, Mohd Omar; R. L., Smith Jr. (Elsevier Inc., 2007)
Extraction of palm kernel oil from dehulled ground palm kernel using supercritical carbon dioxide (SC-CO2) was studied at conditions of 313.2 and 353.2 K and at pressures from 20.7 to 48.3 MPa. The yield of PKO increased with pressure from 34.5 to 48.3 MPa at 353.2 K and attained a value of 49 g oil/100 g palm kernel at 48.3 MPa and 353.2 K. Lower amounts of shorter chain triglycerides component in terms of fatty acid constituents (C8–C14) were extracted at lower pressures of 20.7–27.6 MPa, and higher amounts of longer chain fatty acid constituents (C16–C18:2) were extracted at higher pressures from 34.5 to 48.3 MPa. A simple correlation was developed based on a kinetic mass transfer model. From the correlation, the minimum amount of CO2 usage for a given yield could be estimated.